AN ANALYSIS OF SOCIAL STUDIES COURSE QUESTIONS IN ‘STUDY QUESTIONS’ BOOKS ACCORDING TO THE REVISED BLOOM TAXONOMY (Third Sector Social Economic Review, 2025)
The aim of Bloom’s Taxonomy [BT] is to classify educational objectives in a progressive and hierarchical manner. BT was created by Benjamin Bloom in 1956. In 2001, Anderson et al. organized BT in two dimensions as knowledge and cognitive process dimensions and published it as the Revised Bloom’s Taxonomy [RBT]. The aim of this study is to examine the social studies course questions in the books titled ‘Study Questions’ distributed to schools at the 4th, 5th, 6th and 7th grade level in the 2022-2023 academic year by the Ministry of National Education [MoNE] according to the RBT. The data source of the study consists of 741 multiple-choice questions in a total of 5 books, 2 at the 4th grade level, 1 at the 5th grade level, 1 at the 6th grade level and 1 at the 7th grade level. In the study, document analysis, one of the qualitative research methods, was preferred and the data were evaluated by descriptive analysis. As a result of the research, in all grade levels, the most associations in the knowledge accumulation dimension were made with the knowledge of factual/specific details and elements. In the cognitive process dimension, the most associations were made with the recall/recognition dimension at all grade levels. It was concluded that the social studies course questions in the ‘Study Questions’ books represent the lower level according to the RBT. It was suggested that more questions measuring higher level cognitive dimensions should be prepared in ‘Study Questions’ books.
Keywords: Social studies; Bloom’s Taxonomy; Revised Bloom’s Taxonomy; study questions book; qualitative research.